Leukemia Detection and Classification Based on Machine Learning and CNN: A Review - Rasheed, Hakar Hasan; Abdulazeez, Adnan Mohsin (AI Society & STMIK Indonesia, 2024)
Advancements in data mining methods have significantly improved disease diagnosis, particularly in the realm of leukemia detection. Leukemia, a complex cancer affecting white blood cells, poses significant challenges in diagnosis and management due to its diverse manifestations. Various machine learning algorithms, including Convolutional Neural Networks (CNNs), Support Vector Machines (SVMs), Random Forests (RF), Decision Trees (DTs), K-Nearest Neighbors (K-NN), Logistic regression (LR) and Naïve Bayes (NB) classifiers, have been employed to accurately classify leukemia cases based on diverse datasets and image analyses. This paper provides a comprehensive overview and comparison of these classification techniques, highlighting their effectiveness in diagnosing different leukemia subtypes. Additionally, the paper discusses the methodology and findings of several studies focusing on leukemia detection, emphasizing the significance of machine learning in enhancing diagnostic accuracy and treatment planning. Furthermore, it explores the challenges and future directions in leveraging machine learning for leukemia diagnosis, including the need for standardized datasets, algorithm refinement, and integration with clinical data for personalized treatment strategies.